2009
DOI: 10.1038/ijo.2009.226
|View full text |Cite
|
Sign up to set email alerts
|

Indirect lifestyle intervention through wives improves metabolic syndrome components in men

Abstract: Objectives: It is well known that body weight loss through a direct (supervised) lifestyle intervention (LSI) improves obesityrelated metabolic disorders. The purpose of this study was to investigate the effects of an indirect LSI on weight loss and metabolic syndrome (MetS) in spouses of LSI participants. Methods: A total of 104 men (abdominal circumference X85 cm; age, 52.1 ± 9.3 years) were assigned to one of three groups: no intervention (NI, n ¼ 34), direct intervention (DI, n ¼ 34) or indirect interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…Familial aggregation of MS has been a focus of studies in various populations [10][11][12][13][14][18][19][20][21][22][23][24][25][26][27][28]. The subjects studied in families included parents (i.e., couples), children and relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Familial aggregation of MS has been a focus of studies in various populations [10][11][12][13][14][18][19][20][21][22][23][24][25][26][27][28]. The subjects studied in families included parents (i.e., couples), children and relatives.…”
Section: Discussionmentioning
confidence: 99%
“…3 It is well known that body weight reduction improves metabolic disorders related to obesity, and many studies [4][5][6][7] have indicated that metabolic risk factors, such as blood pressure, lipids and glucose, improve with weight reduction through a short-term weight-loss intervention. However, several studies [8][9][10] have…”
Section: Introductionmentioning
confidence: 99%
“…In a US study among 279 adult men and women with MS, only body weight and waist circumference were significantly decreased by a 12-month computer-based intervention of physical activity and diet 13) . Similarly, Japanese studies among subjects who had at least one component of MS have also observed significant decreases in body weight, fasting glucose or glycated hemoglobin in intervention groups; however, a beneficial effect of intervention on blood pressure, total cholesterol or triglyceride has not been observed [5][6][7] . Among persons with MS, lifestyle intervention was focused on weight control, although physical activity and diet may have a favorable effect on body weight, waist circumference and glucose metabolism but have no or limited effect on blood pressure and lipid profile.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, in an Italian study among subjects with MS and those who had two MS components and a high level of high-sensitivity C-reactive protein (hs-CRP) 4) , the intervention group showed a significantly greater reduction in the prevalence of MS than the control group. In some Japanese studies, lifestyle intervention in adults who had an unfavorable profile in terms of cardiometabolic risk factors [5][6][7] has been shown to improve components of MS. To our knowledge, however, no study has examined the effect of intervention among subjects who met the Japanese definition of MS in Japan. …”
mentioning
confidence: 99%